Pengaruh Pengungkapan Laporan Keberlanjutan dan Profitabilitas Terhadap Manajemen Laba pada Perusahaan Batu Bara di Indonesia periode 2017-2021 - Renaldi, Ricky; Hendriyeni, Nora Sri (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
Nowadays, corporate social responsibility is the common thing that every company does. However, corporations tend to deliver irrelevant information alongside corporate social responsibility activities. Profitability also becomes a reason companies try to manipulate the financial statement with earnings management practices. This study focuses on the impact of sustainability report disclosure and profitability toward earnings management on public Indonesian coal companies in 2017-2021. This study is the causal method. The population in this study used public Indonesian coal companies in 2017-2021. The sample was selected using the purposive sampling method with 15 samples. This study uses corporate governance and the anti-corruption dimension provided by the GRI G4 standard as indicators of sustainability report disclosure, ratio of return of assets as an indicator of profitability, and total periodic accrual value entity as an indicator for earnings management. Results of this study show sustainability report disclosure has no effect on earnings management in this entity; meanwhile, profitability affects the earnings management practices that happened. Future studies may include more aspects of the sustainability of disclosure to the study.